Resolution LM-2011-0361: Feasibility Study for Debit Card Functions - (:unkn) unknown (My University, 2012)
In this Resolution, the Board of Aldermen of the City of New Haven authorize the application to and acceptance of a grant from the First City Fund Corporation (FCFC) to conduct a feasibility study on the potential rollout of debit card functions for the New Haven Elm City Resident Card.
Keywords: Sanctuary Policies; Community Service Administration; Elm City Resident Card Program; Mayor; Debit functionality; Feasibility study